2012
DOI: 10.1557/jmr.2012.32
|View full text |Cite
|
Sign up to set email alerts
|

Structures, dielectric and ferroelectric properties of Sr2-xCaxNaNb5O15lead-free ceramics

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…In this structure mono or divalent cations can be accommodated at the A-sites (A 1 and A 2 ), tri or pentavalent cations at octahedral sites (B 1 and B 2 ) and C-site is generally have small ions or empty. It is expected that the substitutions of varieties of cations at the A and B sites change the crystal structure and physical properties of materials significantly due to their different atomic/ionic size and charge distribution [11][12][13][14][15]. Most of the TB structure belongs to tetragonal or orthorhombic structure with small distortion of multiple perovskites.…”
mentioning
confidence: 99%
“…In this structure mono or divalent cations can be accommodated at the A-sites (A 1 and A 2 ), tri or pentavalent cations at octahedral sites (B 1 and B 2 ) and C-site is generally have small ions or empty. It is expected that the substitutions of varieties of cations at the A and B sites change the crystal structure and physical properties of materials significantly due to their different atomic/ionic size and charge distribution [11][12][13][14][15]. Most of the TB structure belongs to tetragonal or orthorhombic structure with small distortion of multiple perovskites.…”
mentioning
confidence: 99%
“…The ambiguity in the literature as to space groups for SNN may in part relate to structural variations associated with different synthesis conditions. In a further example of the uncertainties in indexing diffraction patterns, a recent study of Ca 2+ modified SNN reports a tetragonal phase for SNN with no Ca 2+ substitution, changing to orthorhombic with increasing levels of Ca 2+ substitution [24,27]. Verification of the true crystal system of SNN produced in our laboratory must await a detailed future study using electron and neutron diffraction.…”
Section: Resultsmentioning
confidence: 91%
“…The perovskite-type NSN phase was also detected using powder X-ray and neutron diffraction in 'filled' TB Sr 2 NaNb 5 O 15 ceramics [21]. Torres-Pardo et al showed that the 'filled' TB SCNN compounds were easily contaminated by the perovskite-type Na 0.5 Sr 0.25 NbO 3 phase due to the solid solution limit [21,22]. According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…have shown that the ceramics with x = 0.15 showed better electrical properties and had application prospects in lead-free electronic components [15,22]. In this work, The phase structure of the prepared ceramics samples was characterized using Xray diffraction (XRD; D/max-2200, Rigaku, Japan, Cu Kα) with a scanning step of 0.02° over a 2θ range of 20-60°.…”
Section: Studies Involving the Effects Of Sr/ca Ratio On Electrical Pmentioning
confidence: 99%